Directions for Optimization of Photosynthetic Carbon Fixation: RuBisCO's Efficiency May Not Be So Constrained After All - Cummins, Peter L.; Kannappan, Babu; Gready, Jill E. (Frontiers in Plant Science, 2018)
The ubiquitous enzyme Ribulose 1,5-bisphosphate carboxylase-oxygenase (Rubisco) fixes atmospheric carbon dioxide within the Calvin-Benson cycle that is utilized by most photosynthetic organisms. Despite this central role, Rubisco’s efficiency surprisingly struggles, with both a very slow turnover rate to products and also impaired substrate specificity, features that have long been an enigma as it would be assumed that its efficiency was under strong evolutionary pressure. Rubisco’s substrate specificity is compromised as it catalyzes a side-fixation reaction with atmospheric oxygen; empirical kinetic results show a trend to tradeoff between relative specificity and low catalytic turnover rate. Although the dominant hypothesis has been that the active-site chemistry constrains the enzyme’s evolution, a more recent study on Rubisco stability and adaptability has implicated competing selection pressures. Elucidating these constraints is crucial for directing future research on improving photosynthesis, as the current literature casts doubt on the potential effectiveness of site-directed mutagenesis to improve Rubisco’s efficiency. Here we use regression analysis to quantify the relationships between kinetic parameters obtained from empirical data sets spanning a wide evolutionary range of Rubiscos. Most significantly we found that the rate constant for dissociation of CO2 from the enzyme complex was much higher than previous estimates and comparable with the corresponding catalytic rate constant. Observed trends between relative specificity and turnover rate can be expressed as the product of negative and positive correlation factors. This provides an explanation in simple kinetic terms of both the natural variation of relative specificity as well as that obtained by reported site-directed mutagenesis results. We demonstrate that the kinetic behaviour shows a lesser rather than more constrained Rubisco, consistent with growing empirical evidence of higher variability in relative specificity. In summary our analysis supports an explanation for the origin of the tradeoff between specificity and turnover as due to competition between protein stability and activity, rather than constraints between rate constants imposed by the underlying chemistry. Our analysis suggests that simultaneous improvement in both specificity and turnover rate of Rubisco is possible